BACTERIAL INFECTION IN THE INDUSTRY OF Giant Tiger Prawn (Penaeus monodon) Larvae in Tarakan City - Cahyadi, Jimmy (Jurnal Harpodon Borneo, 2022)
Tarakan City is a hatchery center for giant tiger prawn larvae production. However, the quality of the larvae produced is still far from expectations, namely free of pathogens free and capable of being resistant to disease. Observation of bacterial infection in the growth phase of giant tiger prawn larvae was carried out to determine the cause and proper treatment in the hatchery. The results showed that the isolation of bacteria in tiger prawns post larvae using 3% TSA media obtained 8 isolates in the Amal Hatchery and 8 isolates in the Beringin Tiga Hatchery with the characteristics of the colonies being cream and yellow in color and the colony shape was irregular, entire, and law conversion. Based on the gram test including gram negative and biochemical tests identified the type; Alcaligenes denitrificans, Pseudomonas diminuta, Shewanella putrefaciens, Bordetella bronchiseptica, Vibrio spp, Alcaligenes faecalis, Flavobacterium breve, Flavobacterium thalpophilum, Flavobacterium multivorum, Pseudomonas pseudoalcaligenes, Pasteurella Pseudomonas.Keywords: Tiger prawn larvae, Bacteria, Hatchery